Development of Learning Media Using Smart Apps Creator Based on Local Wisdom in Work and Energy Materials - Nurmila; Tirtawaty Abdjul; Ritin Uloli (Postgraduate, University of Mataram, 2023)
Technology-based learning media in this era's education field is essential to deliver more exciting and interactive learning that can be linked to local wisdom. This research aims to describe the validity, practicality, and effectiveness of learning media using SAC based on local wisdom on the material of work and energy in 10th grade of SMA Negeri 1 Tinangkung and SMA Negeri 2 Tinangkung. This research uses the development of ADDIE Models. The namely obtained the average percentage validation results for media of 96.67% and material of 96.69% and is in the very valid category, the practicality of learning media used with an average percentage of assessment for small classes of 91.47% and large classes of 97.68% with a very good predicate. The average assessment percentage for learner responses in small classes is 94.46%. In contrast, for large classes, it is 87.14%. The effectiveness of learning media for learner activity observation sheets in small classes is 100%, and in large classes is 99.78%, with a very good predicate. For learning outcomes in the small class, N-Gain was 0.98 with a high category, and the extended class was 0.965 with a very high category.